Performance Evaluation of Dynamic Voltage Restorer Based on Transformer-based Z Source Inverter - Deshpande Chinmay V.; Deshpande Chaitanya V.; Deokar Sanjay A. (Institute of Advanced Engineering and Science, 2017)
In this paper, latest technology is introduced in substitution to conventional voltage and current type inverter with Transformer based impedance (Z) source inverter in voltage sag assessment and mitigation and compared with voltage source inverter based dynamic voltage restorer. Transformer based impedance source inverters (Trans-Z source inverters) are newly proposed inverters that can be used to overcome downside of voltage source inverter, current source inverter and impedance source (Z-source) inverter. T-Z source inverter consists of transformer with high frequency and low leakage inductance along with low reactive component compared with conventional Z source inverter. In case of T-Z source inverter, voltage stress throughout Z-source capacitor is reduced along with inrush current limitation at startup. This paper presents modeling of T-Z source inverter based dynamic voltage restorer using MATLAB/SIMULINK software along with its THD analysis which is compared with VSI based dynamic voltage restorer. Here abc to dq0 control algorithm is employed. The control technique which is employed for simulation shows excellent results for voltage sag and swell compensation.